2010
DOI: 10.1158/0008-5472.can-10-0207
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Complex Component Rictor Interacts with PKCζ and Regulates Cancer Cell Metastasis

Abstract: Epidermal growth factor (EGF) mediates breast cancer cell chemotaxis and metastasis through mechanisms that involve the growth-regulatory mammalian target of rapamycin (mTOR) complex mTORC2, but the mechanisms involved remain obscure. Here, we report that the rapamycin-insensitive mTORC2 component protein Rictor is a critical mediator of metastasis in breast cancer cells. In patients with ductal carcinoma, Rictor expression was associated with increased lymph node metastasis. EGF induced translocation and colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 38 publications
9
107
0
1
Order By: Relevance
“…In tumor cells, EGF may mediate proliferation by activating the EGF receptor pathway which leads to tumor cells survival and metastasis (18). Previous studies demonstrated that EGF is able to induce tumor metastasis through matrix metalloproteinases (19), tyrosine kinase PK2 (20), Podoplanin (21), Rictor binding protein (22), epithelial mesenchymal transition (23) and improving blood vessel (24) and lymph gland growth (25,26). In the present study, the mRNA level of EGF was significantly upregulated in patients with lymph node metastasis, which indicated that EGF may be associated with lymph node metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, EGF may mediate proliferation by activating the EGF receptor pathway which leads to tumor cells survival and metastasis (18). Previous studies demonstrated that EGF is able to induce tumor metastasis through matrix metalloproteinases (19), tyrosine kinase PK2 (20), Podoplanin (21), Rictor binding protein (22), epithelial mesenchymal transition (23) and improving blood vessel (24) and lymph gland growth (25,26). In the present study, the mRNA level of EGF was significantly upregulated in patients with lymph node metastasis, which indicated that EGF may be associated with lymph node metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30. A375 and MUM‐2B cells pre‐treated with scrambled control oligomer (scr) or shRictor were cultured in 6‐well culture plates in a monolayer at 80–90% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Rictor was found to interact with PKCζ and mediates chemotaxis and metastasis in breast cancer cells. 94 However, this rictor function appears to be mTORC2-independent and could occur when rictor expression becomes elevated. In colorectal cancer cells, both mTORC2 and mTORC1 could regulate cell motility and metastasis via the Rho GTPases.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%